Escourolle & Poirier Manual of basic neuropathology - Gray, Françoise; De Girolami, Umberto; Poirier, Jacques (Butterworth-Heinemann, 2004)
The purpose of this manual is to present in a clear, concise, and didactic manner, and illustrate with images in color and with schemes, the broad range of different lesions that affect the nervous system and how diagnosis is reached. After a general description of the basic macroscopic and microscopic changes specific to the nervous system, the different pathological processes which affect the nervous system, i.e., tumors, trauma, strokes, infections, prion diseases, degenerative processes, acquired and hereditary metabolic disorders and developmental malformations, are described. Specific chapters are devoted to epilepsy and the pathology of peripheral nerves, skeletal muscle and pituitary. Each chapter has been written by internationally recognized experts in the field, and provides updated information including genetic as well as basic technical and practical data.
Keywords: patologie; neurologie